Déjà vu and prescience in a case of severe episodic amnesia following bilateral hippocampal lesions. Issue 7 (9th August 2021) - Curot, Jonathan; Pariente, Jérémie; Hupé, Jean Michel; Lotterie, Jean-Albert; Mirabel, Hélène; Barbeau, Emmanuel J.
ABSTRACT: Several studies pertaining to déjà vu have consistently made a connection with the perirhinal region, a region located below the hippocampus. This idea is strengthened by the fact that déjà vu is an erroneous sense of familiarity and that familiarity appears to largely depend on the perirhinal region in healthy subjects. In this context, the role of the hippocampus is particularly unclear as it is unknown whether or not it plays a role in the genesis of déjà vu. We report on the case of OHVR, an epileptic patient who suffers from severe episodic amnesia related to massive isolated bilateral damage to the hippocampus. In contrast, the perirhinal region is intact structurally and functionally. This patient reports frequent déjà vu but also another experiential phenomenon with a prominent feeling of prescience, which shows some of the characteristics of déjà vécu. She clearly distinguishes both. She also developed a form of synaesthesia by attributing affective valence to numbers. This study shows that déjà vu can occur in cases of amnesia with massively damaged hippocampi and confirms that the perirhinal region is a core region for déjà vu, using a different approach from previous reports. It also provides clues about a potential influence of hippocampal alterations in déjà vécu.